The peripatetic journey of teacher preparation in Canada - Bruno-Jofré, Rosa; Stafford, Joseph (Emerald studies in teacher preparation in national and global contexts., 2020)
The Peripatetic Journey of Teacher Preparation in Canada situates teacher training, preparation and education in Canada within national and global histories. The authors lead the reader through an exploration of the objectives of schooling, the contextual role of teachers, and the political undercurrents sustaining various educational conceptions and policies. Taking a 'longue durée' approach, the authors begin by considering traditional practices in Indigenous nations encountered by the colonizers of Canada, including the role of the community as an educator. Tracing teacher preparation through colonization, the authors then move on to the formation of the educational state, the development of educational sciences and educational debate, the professionalization of teaching, its feminization at the elementary level, and its integration into the university, along with changes that emerged out of the 'long 1960s.' The book closes with a discussion of the process by which Indigenous people are reclaiming control over their education, and with it their spirituality, as well as gaining control over the formation of their own teachers. Placing the historical analysis of teacher preparation within prevailing political and socio-economic processes, the authors showcase a series of overlapping discourses and internationally relevant educational trends.